Educação popular e sustentabilidade: um estudo sobre os aspectos educativos não formais no processo de fornecimento de alimentos para a merenda escolar por agricultores familiares, no município de Jacaraú-PB - Ribeiro, Ana Maria Gomes (2022)
Faced with the ecological crisis that threatens life on the planet, alternatives have been thought up in order to build sustainable societies. For example, family farming has produced in an alternative way by adopting agroecological practices, its products have been incorporated into school meals, education has been invoked as environmental education to form the 'ecological subject', etc. In this sense, this work aimed to analyze the non-formal educational aspects present in the process of providing food for school meals by family farmers in the municipality of Jacaraú-PB, taking into account the National School Meals Programme (PNAE). From the point of view of the theoretical framework, the research took into account, for example, elaborations around Popular Environmental Education and Agroecology. Methodologically, it was a qualitative investigation carried out with family farmers and members of the municipal management responsible for school meals, using semi-structured interviews as a means of collecting data. In addition, visits were made to the production and storage units, taking photographic records. The empirical material resulting from the interviews was treated according to the thematic-category content analysis technique, from which the following categories resulted: operationalization of the PNAE from the perspective of food supplying farmers; challenges of production and commercialization in family farming; aspects of local socioeconomic and environmental development in PNAE actions; operationalization of the PNAE from the managers' perspective; protagonists of food supply for school meals by the PNAE; building Popular Environmental Education based on PNAE actions. Among the results, it was found that non-formal educational aspects present in the process of providing food for school meals by family farmers, in the municipality of Jacaraú-PB, relate to information for environmental sustainability, healthy eating and inclusive local development. On the conclusive aspects, it is emphasized that the actions of PNAE stimulate the feeling of collectivity, autonomy and citizen participation, the dissemination of organic/agroecological perspectives and environmental awareness, in a context of learning developed with reference to practice and the exchange of experiences.